The spatio-temporal characteristics and influencing factors of sustainable development in China’s provincial areas - Zhang Qinnan; Tao Chunhai; Xin Yun (Open Geosciences)
The United Nations sustainable development goals aim to promote global industrialization and innovation and achieve sustainable and inclusive economic development by 2030. The sustainable growth of provincial economies has emerged as a critical component of the national plan as China’s economy transitions to a new normal. This article builds an assessment index system encompassing the four "economy–society–ecology–innovation" dimensions to better assess the degree of sustainable economic development in China’s regions. It then uses the gray correlation analysis method to measure and analyze the sustainable economic development of China’s regions from 2006 to 2017. Additionally, the spatial evolution characteristics of each region’s sustainable economic development and spatial pattern are investigated through exploratory spatial data analysis and GIS spatial analysis techniques. This essay seeks to support the region’s economy in achieving sustainable development by offering theoretical underpinnings and useful advice for the creation of successful regional development plans. The study’s findings indicate that in 2017, the assessed value of the level of economic sustainability of China’s regions averaged 0.7156, an increase of 7.3% compared to 2006 while the degree of sustainable economic development in the rest of China, except Inner Mongolia, Shaanxi, and Xinjiang, has steadily increased between 2006 and 2017, the gap between the regions has also widened, with the eastern region having a much higher level of sustainable economic development than the central and western regions. An analysis of the spatial evolution reveals that the degree of sustainable economic development in every region of China generally increases in positive spatial correlation. Its spatial agglomeration is becoming increasingly apparent, with more regions becoming high-high-type and low-low-type agglomerations. Regional wealth disparities, ecological governance capabilities, and technological innovation levels were identified at the local level as essential factors for provincial economic sustainable development, with varying impacts across different regions.